Airway responses to eucapnic hyperpnea, exercise, and methacholine in elite swimmers - Pedersen, L.; Winther, S.; Backer, V.; Anderson, S. D.; Larsen, K. R. (Medicine & Science in Sports & Exercise, 2008)
Purpose: The International Olympic Committee Medical Commission (IOC-MC) requires athletes to provide the result of an objective test to support a diagnosis of asthma or exercise-induced bronchoconstriction (EIB) if they want to inhale a beta-2-agonist. The purpose of the study was to evaluate the airway response to a methacholine challenge and to hyperpnea induced by exercise in the field and in the laboratory or that induced voluntarily by eucapnic hyperpnea in a group of female elite swimmers.